The results of endoscopic tratment in esophageal variceal bleeding - Ülkü SARITAŞ; Emin ALTIPARMAK; Azmi SERİN and Uğur YILMAZ and Çağlar BAYSAL and Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-